Layered cooking device for fruit vinegar raw materials - SONG SHIJIE; SONG QIAOMING (2024)
The utility model provides a layered cooking device for fruit vinegar raw materials, and relates to the technical field of fruit vinegar brewing equipment. The device comprises the tank body and the tank cover covering the tank body, a plurality of layered stirring devices are adopted, the space of the tank body is reasonably utilized, cooking raw materials are arranged in a layered mode, the stirrer is arranged, the raw materials are turned over in the heating process, the motor is arranged at the bottom of the tank body, and the output end of the motor penetrates through the bottom of the tank body and extends into the tank body. The layered stirring device is driven to stir, so that the raw materials are heated more uniformly, the half-cooked condition in the heating process is avoided, and the quality of finished products is improved. 本实用新型提供一种果类醋原料的分层蒸煮装置，涉及果类酿醋设备的技术领域。本实用新型包括罐体以及盖设在罐体上的罐盖，采用多个分层搅拌装置，合理利用罐体空间，将蒸煮原料分层设置，并设置了搅拌器，在加热过程中对原料进行翻滚，罐体的底部设置有电机,电机的输出端贯穿罐体的底部并延伸至其内部，带动分层搅拌装置进行搅拌，使得原料受热更加均匀，避免加热过程中出